Efektivitas Model POGIL Untuk Meningkatkan Efikasi Diri Dan Penguasaan Konsep Larutan Penyangga - Savikha Dhea Neviali; Ratu Betta Rudibyani; Tasviri Efkar (Universitas Lampung, 2021)
The Effectiveness Of POGIL Model to Improve Self Efficacy and Concept Mastery Of Buffer Solution. This research was aimed to describe the effectiveness of POGIL model to improve self efficacy and concept mastery of students’ buffer solution. This study used a quasi-experimental method with pretest-posttest control group design. The population in this study was all students of class XI IPA SMA Negeri 12 Bandar Lampung in 2019/2020 Academic Year. The sample in this study was class XI IPA 3 as experimental class and class XI IPA 4 as control class. The research sample was selected by using cluster random sampling tehnique. The Effectiveness Of POGIL Model is measured to Improve Self Efficacy and Concept Mastery Of Students’ Buffer Solution based on the average significant n-Gain value between the control class and the experimental class. Keywords: POGIL models, self efficacy, mastery of concepts, buffer solution Penelitian ini bertujuan untuk mendeskripsikan efektivitas model POGIL untuk meningkatkan efikasi diri dan penguasaan konsep larutan penyangga peserta didik. Penelitian ini menggunakan metode kuasi eksperimen dengan pretest-postest kontrol group design. Populasi dalam penelitian ini adalah seluruh peserta didik kelas XI IPA SMA Negeri 12 Bandar Lampung Tahun Pelajaran 2019/2020. Sampel dalam penelitian ini adalah kelas XI IPA 3 sebagai kelas eksperimen dan kelas XI IPA 4 sebagai kelas kontrol. Sampel dipilih menggunakan teknik cluster random sampling. Efektivitas model POGIL diukur untuk meningkatkan efikasi diri dan penguasaan konsep peserta didik pada materi larutan penyangga berdasarkan rata-rata nilai n-Gain yang signifikan antara kelas kontrol dan kelas eksperimen.Kata kunci: model POGIL, efikasi diri, penguasaan konsep, larutan penyangga